Alkalinity Effect on Characteristic Properties and Morphology of Magnesium Phosphate Hydrates - Senberber, F. T.; Moroydor Derun, E. (PLEIADES PUBLISHING LTD, 2020)
Magnesium oxide (MgO) and orthophosphoric acid (H3PO4) have been reacted at different pH values to study the effects of alkalinity on the characteristic features of magnesium phosphate material. The phases of the synthesized samples have been identified as newberyite (with the chemical formula of MgHPO4. 3H(2)O and the pdf no. 01-075-1714) and magnesium phosphate hydrate (with the chemical formula of Mg-3(PO4)(2).22H(2)O and the pdf no. 00-044-0775), in the X-ray powder diffraction analyses results. The characteristic band values of samples have been characterized by FTIR and Raman spectroscopies. The differences in morphologies have been studied with Scanning Electron Microscope (SEM). The largest particles in the range of 3.16-9.85 mu m have been seen in the shape of nested flat sheets at pH 10 while the smallest particles between 1.17-2.04 mu m have been obtained in the shape of an ellipse at pH 7. According to the thermogravimetric analyses, the differences in thermal behaviours have been determined. MgHPO4.3H(2)O has lost its crystal water by a two-step reaction while Mg-3(PO4)(2).22H(2)O has dehydrated by a single-step reaction. Obtained results indicate that the crystal structure and surface morphology of the synthesized compound can be modified by the alkalinity of the reaction medium.
Keywords: hydrothermal synthesis; magnesium phosphate; morphology; thermal behaviour; pH; THERMAL-DECOMPOSITION; CERAMICS; RAMAN; Chemistry